Technology of physical rehabilitation of children with bronchopulmonary diseases in the conditions of hospitalization - Івасик, Наталія (Slobozhanskyi Herald of Science and Sport, 2016)
Ivasyk, N. Purpose: the development of technology of physical rehabilitation of children with bronchopulmonary diseases. Material & Methods: general scientific – analysis, conception and generalization, synthesis, comparison, abstraction. Results: technology of physical rehabilitation for children with bronchopulmonary diseases (BD), which is directed to the restoration and the development of physiological functions of a child, the prevention of synchronization of sharp processes, the elimination of negative changes in health of a child, the assistance in creation of conditions for adaptation to changes as a result of disease in life situations, is offered. Conclusions: the program and its activity including basic and variable components is the compound of the offered technology of physical rehabilitation for children with BD in the conditions of hospitalization.